Aktualne standardy diagnostyki i leczenia dolegliwości bólowych miednicy ze źródłem w stawach krzyżowo-biodrowych = Current standards for diagnosis and treatment of pain with pelvis source in sactoiliac joints - Cichosz, Michał; Kochański, Bartosz; Dziweżek, Ireneusz; Kobylańska, Marzena; Polczyk, Artur; Kałużny, Krystian; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Cichosz Michał, Kochański Bartosz, Dziweżek Ireneusz, Kobylańska Marzena, Polczyk Artur, Kałużny Krystian, Zukow Walery. Aktualne standardy diagnostyki i leczenia dolegliwości bólowych miednicy ze źródłem w stawach krzyżowo-biodrowych = Current standards for diagnosis and treatment of pain with pelvis source in sactoiliac joints. Journal of Education, Health and Sport. 2016;6(11):125-136. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164418 http://ojs.ukw.edu.pl/index.php/johs/article/view/3974 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 31.10.2016. AKTUALNE STANDARDY DIAGNOSTYKI I LECZENIA DOLEGLIWOŚCI BÓLOWYCH MIEDNICY ZE ŹRÓDŁEM W STAWACH KRZYŻOWO-BIODROWYCH CURRENT STANDARDS FOR DIAGNOSIS AND TREATMENT OF PAIN WITH PELVIS SOURCE IN SACTOILIAC JOINTS Michał Cichosz1,2, Bartosz Kochański3, Ireneusz Dziweżek4, Marzena Kobylańska5,6, Artur Polczyk7, Krystian Kałużny3, Walery Zukow8 1 Oddział Rehabilitacji Neurologicznej Jolly Med. Popielówek 2 Fundacja Wsparcie Kowary 3 Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 4 Wojewódzki Szpital Specjalistyczny we Wrocławiu ul. Kamińskiego. Zamiejscowy dział Rehabilitacji Leczniczej 5 Katedra Fizjoterapii i Terapii Zajęciowej w Dysfunkcjach Narządu Ruchu. Akademia Wychowania Fizycznego we Wrocławiu 6 Wrocławskie Centrum Rehabilitacji i Medycyny Sportowej 7 Katedra Fizjoterapii, Wydział Nauk o Zdrowiu Uniwersytet Medyczny im. Powstańców Śląskich we Wrocławiu 8 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Stawy krzyżowo-biodrowe (SIJ) są specyficznymi, maziowymi stawami zlokalizowanymi między usznymi powierzchniami kości krzyżowej a dwoma kośćmi biodrowymi. Ich powierzchnia stawowa pokryta jest chrząstką szklistą, która jest szersza powyżej a węższa poniżej. Są one typowym stawem maziowym posiadającym przestrzeń wypełnioną płynem oraz otoczonym torebką stawową. Jednakże różnią się od innych stawów. Główną ich funkcją jest dostarczenie stabilności i zrównoważenie obciążeń występujących między tułowiem a kończynami dolnymi. Stawy te posiadają wysoki poziom stabilności oraz samowzmacniający się mechanizm, który jest związany z anatomicznym kształtem kości (ryglowanie strukturalne) oraz wspierającym działaniem mięśni (ryglowanie siłowe). W pracy przedstawiono aktualne standardy diagnostyki i leczenia dolegliwości bólowych ze źródłem w stawach krzyżowo-biodrowych. Słowa kluczowe: SIJ, PGP, SIJD, LBP Abstract The Sacroiliac Joint (SIJ) is a specyfic, synovial joint between the auricular surfaces of the sacrum bone and the two ilium bones. The auricular surfaces are covered in hyaline cartilage and are broader above and narrower below. The SIJ is also a true diarthrodial joint, as it has a joint space, filled with synovial fluid between the matching articulating surface and a fibrous capsule. However it is different to other diarthrodial joint. The SIJ main roles are to provide stability and offset the load of the trunk to the lower limbs. The SIJ has a high level of stability from the self locking mechanisms of the pelvis, which comes from the anatomy and shape of the bones in the SIJ (Form Closure) and also the muscles supporting the pelvis (Force Closure). The paper presents the current standards of diagnosis and treatment of pain with the source of the sacroiliac joints. Key words: SIJ, PGP, SIJD, LBP